O comportamento informacional de usuários da Biblioteca do SENAC - LAMEIRA, Elane Patrícia Lessa Freitas (2018)
It is about users' use of the SENAC library. It addresses that the informational behavior is related to the search, the use and the handling of information and sources to satisfy the informational needs of the users. It addresses the concept, characteristics and objectives of the study of users in order to demonstrate the literature present in this subject important and relevant to the academic community. The Methodology of this study is exploratory with a qualitative approach and is divided into three phases: bibliographic research, field research and data analysis. Data collection will be performed through questionnaires with a sample of 39 users surveyed, this analysis being qualitative. Renown authors such as Almeida Junior, Amaral, Aquino, Ferreira, Guimarães and others will be cited in this study as theoretical support. It concludes that in general the users of the library are satisfied with the offered services, however some students evaluated how to regulate the equipment of computer science, since the demand of computers does not match with the demand of users. This data as a "regular" evaluation will be a service to be improved in the information unit, when the other services show quality by the analyzed data, so the library is present and active with the purposes of the SENAC institution.